Fructo-oligosaccharides, hydrolyzed soy protein and yeast (Saccharomyces sp.) extract as potential cryoprotectans in gluten-free frozen dough and bread quality. (Research, Society and Development, 2021)
People with celiac disease, wheat allergy, and non-celiac gluten sensitivity required bakery products without gluten. However, gluten-free bread has a high rate of starch retrogradation during shelf life, resulting in loss of softness in the bread crumbs. The inclusion of frozen doughs for gluten-free bread can provide a feasible solution to increase product supply with high technological and sensory quality, providing fresh bread with uniform characteristics. The biggest challenge in the frozen dough for gluten-free bread is related to the high amount of water added to the dough (70-120 % - flour basis) because the ice crystals formed during the freezing step can cause damage to yeast. The use of cryoprotectants in the dough is an alternative for preserving yeast during freezing and cold chain maintenance. This study aimed to evaluate the behavior of fructo-oligosaccharide, hydrolyzed soy protein, and yeast extract as a cryoprotectant in the gluten-free frozen dough and the evaluation of bread quality. Through the Response Surface Methodology, using a Simplex-Centroid Mixture Design, the cryoprotectants were evaluated up to a concentration of 5 % (flour basis) with freezing of the dough for 7 days at -18 °C. The results showed that with the use of cryoprotectants, there was an increase in volume increase of the doughs, in the specific volume of the bread, and the softness of the crumb. The use of 69 % fructo-oligosaccharide and 31 % hydrolyzed soy protein, without the yeast extract, was considered as the optimal formulation for the tested cryoprotectants, with a probability of 79.60 % of success obtained by the desirability function. These levels promoted a better biopreservation of yeast fermentation power and resulting in an improved crumb softness and specific volume at 46 and 40 %, respectively, compared to the standard sample.